Homogalacturonan Accumulation in Cell Walls of the Green Alga Zygnema sp. (Charophyta) Increases Desiccation Resistance - Herburger, Klaus; Xin, Anzhou; Holzinger, Andreas (Frontiers in Plant Science, 2019)
Abstract Land plants inherited several traits from their green algal ancestors (Zygnematophyceae), including a polysaccharide-rich cell wall, which is a prerequisite for terrestrial survival. A major component of both, land plant and Zygnematophyceaen cell walls is the pectin homogalacturonan (HG) and its high water holding capacity may have helped algae to colonize terrestrial habitats, characterised by water scarcity. To test this, HG was removed from the cell walls of Zygnema filaments by pectate lyase (PL) and their effective quantum yield of photosystem II (YII) as a proxy for photosynthetic performance was measured in response to desiccation stress by pulse amplitude modulation (PAM). Old filaments were found to contain more HG and are more resistant against desiccation stress but relatively lose more desiccation resistance after HG removal than young filaments. After rehydration, the photosynthetic performance recovered less efficiently in filaments with a HG content reduced by PL, independently of filament age. Immunolabelling showed that partially or un-methylesterified HG occurs throughout the longitudinal cell walls of both young and old filaments, while no labelling signal occurred when filaments were treated with PL prior labelling. This confirmed that most HG can be removed from the cell walls by PL. The initial labelling pattern was restored after ~3 days. A different form of methylesterified HG was restricted to cell poles and cross cell walls.. In conclusion, it was shown that the accumulation of HG in Zygnema filaments increases their resistance against desiccation stress. This trait might have played an important role during the colonization of land by Zygnematophyceae, which founded the evolution of all land plants.